PRIMARY SCHOOL TEACHER EDUCATION STUDENTS’ ENGLISH COMPETENCE IN WRITING VIEWED FROM ERROR ANALYSIS OF MAKING A COMPOSITION - Umi Sholihah; Suhud Eko Yuwono; Kustinah Kustinah (Lingua, 2022)
This study aims at describing errors on writing of primary school teacher education students (PGSD) Universitas Widya Dharma Klaten to know the students’ English competence. The strategy of the research in this study is descriptive qualitative; and the qualitative data is the students’ writing. The data here are collected from 23 students’ work in making a composition. The erroneous sentences analyzed based on three classifications, namely the surface strategy taxonomy, influencing language switch, and students’ writing skill. The writers analyze the data carefully to find errors. The errors are divided according to its classification. Based on the data findings, the writers found that from 26 students of primary school teacher education (PGSD) Unwidha there are 23 students made some errors, two students made a good composition without any error, and one student didn’t write the composition. The researchers finally list 76 errors of students’ writing. The writers conclude that there are 35 errors (46.052%) based on the surface strategy taxonomy, 9 errors (11.842%) based on influencing language switch, and 32 errors (42.105%) based on students’ writing skill.